REFORMASI PENDIDIKAN: IMPLIKASINYA DALAM TEKNOLOGI PENDIDIKAN ISLAM - Chairul Amriyah, Ade Vera Yantika, Ahmad Ilham Fadli, Ahmad Syafak Khoirut Tobib; Bagas Armayoga, Dimas Raba Pramodana, Agus Jatmiko, Meriyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Educational reform is a systematic process of changing the education system to adapt to the evolving needs of society and technological advancements. In the context of Islamic education, this reform is crucial to ensure that Islamic values remain relevant and applicable in the digital age. This article explores the implications of educational reform on the integration of technology in Islamic education. Using a qualitative approach and literature review as the primary method, the study finds that technology integration enhances the effectiveness of learning, expands access, and enriches teaching methods. However, successful implementation requires adequate preparation in terms of teachers’ competencies, curriculum development, and supporting infrastructure, all while maintaining alignment with Islamic principles.